Grassroots interventions for alcohol use disorders in the Mexican immigrant community: A narrative literature review. Issue 3 (4th August 2022) - Garcia, Victor; Lambert, Emily; Fox, Katherine; Heckert, Daniel; Pinchi, Nahomy Hidalgo
Abstract: This narrative literature review addresses grassroots interventions for alcohol use disorders as practiced in Mexican immigrant communities. These organic efforts are 24-hour AA groups, or anexos, fourth and fifth step AA groups, juramentos, and curanderismo . Literature was identified using PubMed and CINAHL and limited to works published from 2000 to 2018. In all, three publications on 24-hour groups were found, two on fourth and fifth step groups, four on juramentos, and one on curanderismo use. The review offers insight on their practices and concludes that the interventions' cultural resonance provides advantages over cultural competency AUDs programs developed in public health.